Comparison of Saliva and Nasopharyngeal Swabs for SARS-CoV-2 Detection in an Emergency Department and Ambulatory Testing Locations. (28th October 2021) - Attaway, C; El-Sharkawy Navarro, F; Richard-Greenblatt, M; Herlihy, S; Gentile, C; Glaser, L; Morris, B; Abella, B; Collman, R
Abstract: Introduction/Objective: Nasopharyngeal (NP) swabs have been the traditional specimen source used for testing for respiratory viruses. However, at the start of the COVID-19 pandemic, several studies suggested that saliva could also be used as a specimen source for testing for SARS-CoV-2. Despite potential benefits, there was limited data on the characteristics of this specimen type and few commercial assays with FDA emergency use authorization allowed saliva as a specimen source. In order to explore the feasibility and validate using saliva as a specimen source for ambulatory and emergency department patients we designed a study to compare saliva to NP swabs for SARS-CoV-2 testing. Methods/Case Report: Specimens were collected in the emergency department and ambulatory testing sites between May 6, 2020-July 7, 2020. Nasopharyngeal swabs were collected as part of routine clinical practice and patients were given written instructions to self-collect 1mL of saliva into a sterile specimen cup with or without a straw. SARS-CoV-2 testing was performed in parallel with both specimen types using the TaqPath COVID-19 Combo Kit (Thermo Fisher Waltham, MA). Saliva was diluted 1:1 in saline prior to testing. Specimens were transported to the lab at 4C and frozen at -80C prior to testing. Results (if a Case Study enter NA): Seventy-four patients had both an NP swab and saliva tested in this study. Thirty of the 74 patients (41%) were unable to produce the full 1mL of saliva requested, but all samples had sufficient volume for testing after dilution. There were 34 positive samples obtained with an 82% positive agreement between the NP swabs and saliva. In 6 cases, the NP swab was positive, and the paired saliva was negative. In 1 case, only the saliva was positive. The average Ct of the positive NP swabs with a paired negative saliva sample was 39.6. There was only a single invalid test for one of the saliva samples. Conclusion: Saliva was a straightforward sample to collect and test for SARS-CoV-2. Challenges included obtaining sufficient sample and a less predictable matrix that required dilution to ensure proper pipeting. In this study, NP swabs were more sensitive for detection of SARS-CoV-2. Paired saliva was more often negative in patients shedding small amounts of SARS-CoV-2 based on a high Ct of the positive NP sample.